2010
DOI: 10.1007/s00417-010-1352-7
|View full text |Cite
|
Sign up to set email alerts
|

Fundus autofluorescence and spectral-domain optical coherence tomography findings of leopard spots in nanophthalmic uveal effusion syndrome

Abstract: Okuda et al. FAF and SD-OCT findings of leopard spots in uveal effusion-1 - -----------Case Report----------- Fundus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…HDS in the ICGA have also been observed in other disorders such as nanophthalmos, uveal effusion syndrome, posterior scleritis, angioid streaks, and a rare case of central serous chorioretinopathy [22][23][24][25][26]. HDS in our case series were different from other disorders in that there were no fundus changes such as Leopard spots and no permanent retinal pigment epithelial changes.…”
Section: Discussionmentioning
confidence: 42%
“…HDS in the ICGA have also been observed in other disorders such as nanophthalmos, uveal effusion syndrome, posterior scleritis, angioid streaks, and a rare case of central serous chorioretinopathy [22][23][24][25][26]. HDS in our case series were different from other disorders in that there were no fundus changes such as Leopard spots and no permanent retinal pigment epithelial changes.…”
Section: Discussionmentioning
confidence: 42%
“…HDS in the ICGA have also been observed in other disorders such as nanophthalmos, uveal effusion syndrome, posterior scleritis, angioid streaks, and a rare case of central serous chorioretinopathy [21][22][23][24][25]. HDS in our case series were different from other disorders in that there were no fundus changes such as Leopard spots and no permanent retinal pigment epithelial changes.…”
Section: Discussionmentioning
confidence: 42%
“…[ 17 , 18 ] Leopard spots by proliferation and migration of RPE cells are observe in uveal effusion syndrome, [ 5 ] that are presented by multiple hypofluorescent spots on FA and ICGA. [ 6 , 17 , 18 ] Furthermore, Okuda et al [ 19 ] reported FAF images of leopard spots showing hyperautofluorescence in a patient with uveal effusion syndrome. In our patient, the eyeball size was not small but normal or rather large, and the findings of fundus, angiographic and FAF images were consistent with those of uveal effusion syndrome.…”
Section: Discussionmentioning
confidence: 99%